The effect of pouring time on the dimensional accuracy of casts made from different irreversible hydrocolloid impression materials - Supneet Singh Wadhwa; Richa Mehta; Nidhi Duggal; Kamlesh Vasudeva (Wolters Kluwer Medknow Publications, 2013)
Aims and Objectives: To determine the time dependent accuracy of casts made from three different irreversible hydrocolloids. Materials and Methods: The effect of delayed pouring on the accuracy of three different irreversible hydrocolloid impression materials - Regular set CA 37(Cavex, The Netherlands), regular set chromatic (Jeltrate, Dentsply), and fast set (Hydrogum soft, Zhermack Clinical) was investigated. A brass master die that contained two identical posts simulating two complete crown-tapered abutment preparations with reference grooves served as a standardized master model. A total of 120 impressions were made using specially prepared stock-perforated brass tray with 40 impressions of each material. The impressions were further sub-grouped according to four different storage time intervals: 0 min (immediately), 12 min, 30 min, and 1 h. The impressions were stored at room temperature in a zip-lock plastic bag. Interabutment and intraabutment distances were measured in the recovered stone dies (Type IV, Kalrock) using a profile projector with an accuracy of 0.001 mm. The data so obtained was analyzed statistically. Results: Results of this study showed no statistically significant differences in the accuracy of casts obtained at different time intervals. Conclusion: Because it is not always possible to pour the impression immediately in routine clinical practice, all irreversible hydrocolloid materials studied could be stored in a zip-lock plastic bag for upto 1 h without any significant distortion.